Implementation of Fuzzy Logic on Watering Automation System for Palm Tree Planting Media Based on WSN - Rafi Muflih, Muhammad Farras; Muzzakhim Imamuddin, Azam; Kusumawardani, Mila (Politeknik Negeri Malang, 2023)
Currently, date palm farmers manually assess soil color and dryness without a definitive reference. Manual watering of date palms persists, although some gardens employ irrigation systems. The absence of communication infrastructure in plantations necessitates flexible network technology. The system comprises a DS18B20 soil temperature sensor and FC-28 soil moisture sensor. Temperature and humidity values identify soil dryness, determining water volume for date palm irrigation. Sensor data is stored on Arduino Uno, undergoes pre-programmed processing, and is then transmitted to the sink node via the LoRa Ra-02 communication module. The results of system testing can be concluded that the temperature and humidity sensors can detect the temperature and humidity of the growing media with a fairly small error rate. The use of fuzzy logic inference and watering automation goes according to plan. It is known that for a soil temperature of 25.31°C and soil moisture of 20%RH, the output volume of watering through the hardware is 15,31 liters. The communication module used as a data sender can also run well and stable at a range of up to 200 meters with RSSI = -105 and SNR = -7,1.